Analisis Potensi Riam Jolan sebagai Sumber Air Baku IPA Jagoi Babang Kabupaten Bengkayang - Uray Adisti Ratnasari Asikin; Kiki Prio Utomo; Ulli Kadaria (Bioscientist : Jurnal Ilmiah Biologi, 2023)
One of the problems with the need for clean water in each region is the inadequate availability of existing raw water. The Jagoi Babang WTP is one of the Clean Water Treatment Plants that once operated with a discharge of 30 liters/second, but it stopped temporarily because the previous source of raw water, namely the Gombul River, did not have sufficient discharge, causing raw water needs to not be met. There is an alternative source of raw water in Jagoi Village, namely Riam Jolan, physically the water quality is very clear, and the flow is very adequate. The aim of this research is to determine the availability and quality of raw water in Riam Jolan. The research approach applied is descriptive quantitative by analyzing the availability of raw water using the mock method with a probability of 99%, analyzing instantaneous discharge, and testing the quality of raw water. The results of this research show that the calculation of reliable discharge using the Mock model with a probability of 99% Riam Jolan obtained the maximum reliable discharge in December, namely 0.0227 m3/second or 22.7 liters/second, and the minimum reliable discharge in September was 0.0018 m3/second or 1.8 liters, then the instantaneous discharge calculation shows a figure of 0.0855 m3/s or the equivalent of 85.5 liters/second, the instantaneous discharge obtained meets the raw water requirements for the Jagoi Babang WTP. The results of the Riam Jolan water quality laboratory test show that the water is suitable for use as a clean water source and meets water quality class I.